2013
DOI: 10.1371/journal.pone.0055711
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Obesity during the Preconception and Early Life Periods Alters Pancreatic Development in Early and Adult Life in Male Mouse Offspring

Abstract: Maternal obesity induced by a high fat (HF) diet may program susceptibility in offspring, altering pancreatic development and causing later development of chronic degenerative diseases, such as obesity and diabetes. Female mice were fed standard chow (SC) or an HF diet for 8 weeks prior to mating and during the gestational and lactational periods. The male offspring were assessed at birth, at 10 days, and at 3 months of age. The body mass (BM) gain was 50% greater before pregnancy and 80% greater during pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 66 publications
0
34
0
Order By: Relevance
“…In reference to these studies, mice maintained on a HFD throughout preconception, gestation, and lactation showed pancreas remodeling and beta cell hypertrophy that restored beta cell mass at the end of organogenesis (14). Maintenance or altering the diet after weaning and particularly HFDs during pregnancy structurally altered beta cells in progeny (15).…”
Section: Hf Programming Generates Variable Diabetogenic Phenotypes Inmentioning
confidence: 98%
“…In reference to these studies, mice maintained on a HFD throughout preconception, gestation, and lactation showed pancreas remodeling and beta cell hypertrophy that restored beta cell mass at the end of organogenesis (14). Maintenance or altering the diet after weaning and particularly HFDs during pregnancy structurally altered beta cells in progeny (15).…”
Section: Hf Programming Generates Variable Diabetogenic Phenotypes Inmentioning
confidence: 98%
“…The intrauterine effect of maternal obesity on offspring obesity is difficult to isolate in human studies, but animal experiments support biological plausibility. Diet-induced obesity among pregnant rodents altered offspring adipocyte metabolism to favour hypertrophy via epigenetic modifications [71][72][73][74]. Other pathways include the effect of maternal obesity on placental function [75], glycaemic regulation [76] and stem cell differentiation [77][78][79][80][81].…”
Section: Maternal Obesitymentioning
confidence: 99%
“…Manual point counting and computational feature extraction have been used to analyze digital images. Morphometry is commonly used for quantitation of histological features (Bringhenti et al 2013; Frantz et al 2013) aided by programs such as STEPanizer and Image-Pro Plus (Tschanz et al 2011; Bringhenti et al 2013; Frantz et al 2013). Although visual-based assessment is the current standard for quantitation of histological features, it is time consuming, tedious, and vulnerable to inter- and intraobserver variability.…”
Section: Introductionmentioning
confidence: 99%